Impact of FDG-PET Computed Tomography for Surgery of Recurrent or Persistent Differentiated Thyroid Carcinoma - Weber, T.; Ohlhauser, D.; Hillenbrand, A.; Henne-Bruns, D.; Reske, S. N.; Luster, M. (Hormone and Metabolic Research, 2012)
Fluorodeoxyglucose-positron emission tomography (FDG-PET)/computed tomography (CT) is able to localize persistent or recurrent disease in differentiated thyroid carcinoma (DTC). The aim of the study was to correlate PET/CT results with precise intraoperative localization of persistent or recurrent papillary and follicular thyroid carcinoma. Patients with differentiated thyroid carcinoma who received FDG-PET scans were prospectively documented. The PET/CT results were correlated with other localization studies (neck ultrasound, 131I whole-body scan) and accurately compared to intraoperative findings and histopathological examinations. FDG-PET/CT scans were performed in 18 patients, between 16 and 84 years of age, from December 2008 to June 2011. Fourteen patients had papillary thyroid carcinomas and 4 had follicular thyroid carcinomas. All patients had a previous thyroidectomy and radioiodine ablation. Before cervical re-exploration, FDG-PET/CT-positive findings were reported in 14 individuals, whereas 4 PET scans provided no evidence of disease. Intraoperatively, 13 of 14 FDG-PET/CT-positive localizations of recurrent or persistent thyroid carcinomas were verified and confirmed by histopathology (sensitivity 93%). In another patient lymph node metastases of lung cancer were detected intraoperatively. However, FDG-PET/CT underestimated the number of lesions in 5 of 6 patients undergoing systematic lymphadenectomy. No lymph node or soft tissue metastases were found intraoperatively in 3 of the 4 patients with negative FDG-PET scans. A solitary cystic lymph node metastasis was found in the fourth patient but was not detected by FDG-PET/CT (specificity 75%). FDG-PET/CT has high sensitivity and specificity for the detection of persistent or recurrent differentiated thyroid carcinoma. FDG-PET/CT helps to select patients who might benefit from surgery because it provides precise anatomical details.
Keywords: papillary thyroid carcinoma; follicular thyroid carcinoma; recurrent thyroid carcinoma; persistent thyroid carcinoma; FDG-PET/CT